Systemic immune effects of anesthetics and their intracellular targets in tumors - Luan, Ting; Li, Yi; Sun, Lihui; Xu, Siqi; Wang, Haifeng; Wang, Jiansong; Li, Chong (Frontiers in Medicine, 2022)
According to the result released by the World Health Organization (WHO), non-communicable diseases have occupied four of the top 10 current causes for death in the world. Cancer is one of the significant factors that trigger complications and deaths; more than 80% cancer patients require surgical or palliative treatment. In this case, anesthetic treatment is indispensable. Since cancer is a heterogeneous disease, various types of interventions can activate oncogenes or mutate tumor suppressor genes. More and more researchers believe that anesthetics have a certain effect on the long-term recurrence and metastasis of tumors, but it is still controversial whether they promote or inhibit the progression of cancer. On this basis, a series of retrospective or prospective randomized clinical trials have been conducted, but it seems to be difficult to reach a conclusion within 5 years or longer. This article focuses on the effects of anesthetic drugs on immune function and cancer and reviews their latest targets on the tumor cells, in order to provide a theoretical basis for optimizing the selection of anesthetic drugs, exploring therapeutic targets, and improving the prognosis of cancer patients.